Statistical sampling and feature selection for epilepsy pattern recognition - Gaidar, V.O.; Sudakov, O.O. (Доповіді НАН України, 2020)
Epilepsy is one of the most common neurological diseases that has broad spectrum of debilitating medical and social
consequences. The automatic forecasting and detecting systems are vitally important, since they allow patients to
avoid dangerous activities in advance of the seizure. We present some methods of feature extraction and selection
for detecting the epileptiform activity in electroencephalography signals, based on the processing of a non-stationary
signal. The proposed approach is based on the application of the Discrete Wavelet Transform (DWT) and signal
processing techniques in order to create the feature vector. Afterwards, the principal component analysis and support
vector machine techniques are used in order to reduce the dimensionality of the feature vector. Епілепсія — одне з найпоширеніших неврологічних захворювань, яке має широкий спектр когнітивних
та соціальних проявів. У представленій статті застосовано методи виділення та відбору статистичних
ознак інтракраніального електроенцефалографічного сигналу для виявлення епілептичної активності
та її ранньої діагностики. Запропонований підхід базується на застосуванні дискретного вейвлет-перетворення та методах обробки сигналів для створення вектора ознак. Метод головних компонент та метод
опорних векторів використано для зменшення розмірності вектора ознак та бінарної класифікації. За результатами роботи вектор з тринадцяти компонент було зменшено до вектора з п'яти компонент зі збереженням специфічності та чутливості класифікації. Эпилепсия — одно из самых распространенных неврологических заболеваний, которое имеет широкий
спектр когнитивных и социальных проявлений. В представленной статье применены методы выделения и
отбора статистических признаков интракраниального электроэнцефалографического сигнала для обнаружения эпилептической активности и ее ранней диагностики. Предложенный подход основан на применении дискретного вейвлет-преобразования и методах обработки сигналов для создания вектора признаков. Метод главных компонент и метод опорных векторов применены для уменьшения размерности
вектора признаков и бинарной классификации. По результатам работы вектор из тринадцати компонент
был уменьшен до вектора из пяти компонент с сохранением специфичности и чувствительности классификации.